Cladding tube for lithium cold space nuclear reactor and preparation method of cladding tube

By using the sandwiched structure clad tube design composed of W-Re alloy, SiCf/SiC composite material and WSi2 coating in the lithium-cold space nuclear reactor, the problems of poor airtightness and corrosion resistance of SiCf/SiC composite material at high temperatures are solved, and a clad tube with high airtightness and corrosion resistance are achieved.

CN119541911AActive Publication Date: 2025-02-28HUNAN INSTITUTE OF ENGINEERING

Patent Information

Application Number
CN202510084043.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-28
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The SiCf/SiC composites in lithium-cooled space nuclear reactors have poor airtightness and reduced corrosion resistance, and are prone to react with UO2 and liquid lithium at high temperatures.

Method used

The clad tube design adopts a sandwich structure, in which the W-Re alloy is the inner and outer tube layer, the SiCf/SiC composite material is the intermediate layer, and the WSi2 coating is the transition layer between the W-Re alloy and the SiCf/SiC composite material to improve airtightness and corrosion resistance.

Benefits of technology

It significantly improves the airtightness and corrosion resistance of the clad tube, ensures that it does not react with UO2 and liquid lithium in high temperature environments, and achieves both strength, lightweight, corrosion resistance and sealing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119541911A_ABST
    Figure CN119541911A_ABST
Patent Text Reader

Abstract

The invention discloses a cladding tube for a lithium cold space nuclear reactor and a preparation method of the cladding tube, and belongs to the technical field of cladding tube structures, and the cladding tube is of an interlayer structure formed by sequentially overlapping a first W-Re alloy layer, a first WSi2 coating, a SiCf / SiC composite material layer, a second WSi2 coating and a second W-Re alloy layer from inside to outside. According to the invention, the air tightness and corrosion resistance of the cladding tube are obviously improved, and the cladding tube for the lithium cold space nuclear reactor has the properties of strong toughness, light weight, corrosion resistance, sealing property and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cladding tube structures, and in particular relates to a cladding tube for a lithium-cooled space nuclear reactor and a preparation method thereof. Background Art

[0002] SiC f SiC composite materials are considered to be ideal materials for nuclear fuel cladding tubes in future nuclear reactors due to their excellent high temperature stability, corrosion resistance, high strength and high modulus. f The good thermal conductivity of SiC composite materials is very important for nuclear reactor systems that require rapid heat transfer. Through effective thermal management, the nuclear reactor can be prevented from overheating and its normal operation can be ensured. f The electrical insulation of SiC composite materials can prevent current leakage in nuclear reactors, which need to prevent current leakage, ensuring the safety of the system. f / SiC composite materials also have broad application prospects in the field of nuclear energy protection. Now the material has become an ideal candidate material for coating nuclear fuel elements and nuclear reactor control rods.

[0003] However, SiC core cladding tubes f / SiC composite materials face the technical bottleneck problem of poor airtightness, and nuclear fuel coating materials are the first barrier to prevent the diffusion of radiation products. f / SiC composite materials are not suitable for direct use as nuclear fuel cladding.

[0004] At present, in the country, there are many researches on improving SiC f There are related studies on the air tightness of SiC / SiC composite materials. For example: The Chinese patent with the authorization announcement number CN114057501B discloses a high-density erosion-resistant ceramic-based composite material and its preparation method. By adding a high-temperature opening treatment step during the matrix densification process, and then applying an ultra-high temperature ceramic coating on the densified matrix, the density and temperature resistance of the ceramic-based composite material are improved, thereby improving the material's erosion resistance and ablation resistance. However, the manufacturing process is complicated, and the current design temperature of lithium-cooled space reactors is very high, up to 1546K and above. Lithium and uranium are active metals. When ceramic-based composite materials come into contact with lithium or uranium at high temperatures, they are prone to react, resulting in a decrease in material performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a cladding tube for a lithium-cooled space nuclear reactor and a preparation method thereof to improve the airtightness and corrosion resistance.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A cladding tube for a lithium-cooled space nuclear reactor, the cladding tube is composed of a first layer of W-Re alloy layer, a first layer of WSi2 coating, a SiC f The / SiC composite material layer, the second WSi2 coating layer and the second W-Re alloy layer are stacked to form a sandwich structure.

[0007] As a further improvement, the mass fraction of rhenium in the W-Re alloy is 20-30%.

[0008] As a further improvement, the thicknesses of the first W-Re alloy layer and the second W-Re alloy layer are 0.015-0.02 mm and 0.02-0.04 mm respectively; the SiC f The thickness of the / SiC composite material layer is 0.01-0.03mm.

[0009] As a further improvement, the thicknesses of the first WSi2 coating layer and the second WSi2 coating layer are 0.01-0.02 mm and 0.02-0.03 mm respectively.

[0010] The present invention also provides a method for preparing the cladding tube for the lithium-cooled space nuclear reactor, comprising the following steps: S1. Preparing a W-Re alloy thin-walled tube to form a first W-Re alloy layer; S2. Preparing a WSi2 coating on the outer surface of a W-Re alloy thin-walled tube to form a first layer of WSi2 coating; S3. Coating SiC on the first WSi2 coating f / SiC composite material layer; S4. Preparing a WSi2 coating on the outer surface of the SiC / SiC composite material layer to form a second layer of WSi2 coating; S5. Prepare a W-Re alloy thin-walled tube on the outer surface of the second WSi2 coating to form a second W-Re alloy layer.

[0011] As a further improvement, S2 includes: pre-placing ball-milled WSi2 powder on a W-Re alloy thin-wall tube for sintering, and repeating the process multiple times until a first layer of WSi2 coating of a desired thickness is formed; S4 includes: pre-placing ball-milled WSi2 powder on the SiC / SiC composite material layer and sintering, and repeating the process multiple times until a second WSi2 coating layer of a desired thickness is formed.

[0012] As a further improvement, the sintering temperature is 1200-1800° C., and the sintering time is 2-3 hours.

[0013] As a further improvement, S3 includes: weaving a SiC fiber preform on the outer surface of the first WSi2 coating layer, then depositing a pyrolytic carbon PyC interface on the SiC fiber preform using a CVI process, and then densifying the SiC fiber preform matrix using a melt infiltration method to prepare a SiC matrix.

[0014] As a further improvement, the CVI process has a deposition temperature of 800-900° C., a deposition pressure of 2-5 kPa, a deposition time of 20-50 h, and a PyC interface with a thickness of 100-300 nm.

[0015] As a further improvement, the melt infiltration method includes: pre-sintering the SiC fiber preform with the PyC interface deposited at 600-800°C, immersing it in molten SiC for 90-120 minutes, and then cooling and solidifying it to form a densified SiC matrix.

[0016] Compared with the prior art, the present invention has the following beneficial effects: In order to overcome the corrosion resistance of lithium-cooled space nuclear reactor cladding tube materials in high temperature environments, SiC f / SiC composite materials are prone to react with UO2 and liquid lithium at high temperatures. The cladding tube sandwich structure of the present invention is composed of W-Re alloy as the inner tube layer and the outer tube layer, SiC f / SiC composite material is the middle tube layer, and the WSi2 coating is W-Re alloy and SiC f / SiC composite material. f The / SiC composite material is located in the middle tube layer. Under high temperature strength, it is protected by the tungsten-rhenium alloy, maintaining mechanical strength and playing a lightweight role. The W-Re alloy maintains the airtightness of the cladding tube in the inner and outer tube layers, protecting the SiC f / SiC composites are protected from corrosion by uranium and liquid lithium.

[0017] As a super alloy material, tungsten-rhenium alloy not only has excellent corrosion resistance but also good sealing performance, which can effectively solve the problem of SiC f / SiC composite materials are not suitable for direct contact with lithium and uranium and have poor airtightness. However, the study found that the cladding tube is lined with W-Re alloy as the metal inner and outer linings, and SiC f / SiC composite material is the middle tube material, which will produce W-Re alloy and SiC f / SiC composite materials will react at the interface at high temperatures, affecting their air tightness and corrosion resistance.

[0018] To solve this problem, the two layers of WSi2 coating of the present invention are both on W-Re alloy and SiC f / SiC composite material middle, isolated SiCf / SiC composites and W-Re alloys, minimizing the use of W-Re alloys and SiC f / SiC composites react, thereby corroding the W-Re alloy.

[0019] The present invention significantly improves the air tightness and corrosion resistance of the cladding tube, and achieves the cladding tube for lithium-cooled space nuclear reactors with a balance of strength, toughness, lightness, corrosion resistance, and sealing properties.

[0020] The nuclear fuel cladding tube of the present invention is mainly used for forming and protecting nuclear fuel rods in lithium-cooled space nuclear reactors, and can also be applied to national defense and military fields, such as rocket launchers, lightweight high-pressure hydrogen storage containers, and accident-tolerant cladding tubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 It is a schematic diagram of the sandwich structure of a cladding tube for a lithium-cooled space nuclear reactor according to an embodiment of the present invention. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0024] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0025] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0026] The cladding tube for a lithium-cooled space nuclear reactor of the present invention comprises, from the inside to the outside, a first layer of W-Re alloy layer, a first layer of WSi2 coating layer, and a SiC f The / SiC composite material layer, the second WSi2 coating layer and the second W-Re alloy layer are stacked to form a sandwich structure.

[0027] The W-Re alloy is a superalloy material composed of tungsten and rhenium, and the rhenium content (wt) in the tungsten-rhenium alloy is preferably 20-30%. The recrystallization temperature of the tungsten-rhenium alloy is 2073k, and the allowable temperature is high; at a high temperature of 1644K, the tensile strength of the tungsten-rhenium alloy is in the range of 466-546MPa; high-temperature lithium corrosion experiments show that the tungsten-rhenium alloy has good compatibility with liquid lithium below 1927°C; the tungsten-rhenium alloy lithium heat pipe has undergone a life test of up to 10,000 hours at 1602°C (1875K) without damage; and the tungsten-rhenium alloy profile preparation process is mature and has good welding performance. The present invention uses a refractory metal W-Re alloy to improve the lithium corrosion resistance of the cladding tube for lithium-cooled space nuclear reactors. The use of tungsten-rhenium alloy as the inner and outer linings of the cladding tube effectively avoids SiC f The / SiC composite material reacts with UO2 and liquid lithium at high temperature, improving the lithium corrosion resistance, radiation resistance and sealing of the cladding tube.

[0028] The WSi2 coating is a high temperature oxidation resistant coating of a W alloy. In the present invention, in order to prevent the tungsten-rhenium alloy and the ceramic matrix composite material (SiC f / SiC) will react at the interface at high temperature to generate WC2, which will corrode the tungsten-rhenium alloy matrix. It is necessary to prepare a WSi2 coating on the surface of the tungsten-rhenium alloy tube layer. The cladding tube for lithium-cooled space nuclear reactor of the present invention uses WSi2 coating as a tungsten-rhenium alloy and SiC f The interlayer of / SiC composite material solves the technical difficulty of the reaction between SiC and tungsten-rhenium alloy at high temperature.

[0029] The SiC f / SiC composite material is the third generation of SiC fiber with high high temperature strength and excellent radiation resistance. f / SiC composite materials. The third generation SiC f / SiC has stable tensile properties at 250~350MPa (1723K), and its deformation is less than 0.1% within 300h at 48MPa (1723K); it has excellent neutron irradiation resistance at 573~1573K, and its strength change before and after irradiation (irradiation dose: 1-40dpa) is less than 20%; the service temperature of the third-generation SiC fiber exceeds 1900K, and its preparation and processing technology are mature; and SiC f / SiC composite material has lightweight performance. The cladding tube for lithium-cooled space nuclear reactor of the present invention adopts SiC f / SiC composite material is used as the intermediate tube layer material of the metal cladding tube, which has a lightweight design and improves the high-temperature strength of the cladding tube.

[0030] In some embodiments, the thickness of the inner and outer W-Re alloy layers is 0.015-0.02 mm and 0.02-0.04 mm respectively. The thickness of the inner and outer WSi2 coating layers is 0.01-0.02 mm and 0.02-0.03 mm respectively. The middle layer SiC f The thickness of the / SiC composite material layer is 0.01-0.03mm.

[0031] In some embodiments, the cladding tube for a lithium-cooled space nuclear reactor is 1-1.5 m long.

[0032] In the sandwich structure of the present invention, the W-Re alloy mainly plays a role in resisting uranium corrosion and lithium corrosion, and the SiC f / SiC composite materials mainly play the role of lightweight, sealing and leak-proofing, while WSi2 coating mainly solves the problem of W-Re alloy and SiC f The difficulty of W-Re alloy being corroded by W-Re alloy is that W-Re alloy reacts with SiC composite material at high temperature to generate tungsten carbide. f / SiC composites react, and SiC f / SiC composite materials are prone to react with UO2 in nuclear reactors and liquid lithium.

[0033] In some specific embodiments, the method of the present invention for a cladding tube for a lithium-cooled space nuclear reactor comprises the following steps: S1. Prepare a W-Re alloy thin-wall tube to form a first W-Re alloy layer.

[0034] The tungsten-rhenium alloy billet can be processed by a thin-wall tube rolling process, such as cold rolling, hot rolling or extrusion process, to prepare a tungsten-rhenium alloy thin-wall tube matching the size of the inner tube layer. In some embodiments, the tungsten-rhenium alloy billet is a W-25Re alloy billet.

[0035] S2. Prepare a WSi2 coating on the outer surface of the W-Re alloy thin-walled tube to form a first layer of WSi2 coating.

[0036] The WSi2 coating can be prepared by ball milling. In some embodiments, the WSi2 powder is first ball milled and dried. Then the ball milled WSi2 powder is pre-placed on the W-Re alloy thin-walled tube for sintering, and the process is repeated multiple times until a first layer of WSi2 coating of a desired thickness is formed.

[0037] In some embodiments, the ball milling time is 4-8 hours, and the ball milling speed is 300-500 r / min. The drying process is: first drying at 60° C. for 24 hours, and then drying at 110° C. for 12 hours to fully remove moisture and impurities in the powder.

[0038] In some embodiments, the sintering temperature is 1200-1800° C., and the sintering time is 2-3 hours.

[0039] S3. SiC coated outside the first layer of WSi2 coating f / SiC composite material layer.

[0040] In some embodiments, a SiC fiber preform is woven on the outer surface of the first WSi2 coating, and then a pyrolytic carbon PyC interface is deposited on the SiC fiber preform by a CVI process, and then the SiC fiber preform is densified by a melt infiltration method to prepare a SiC matrix, thereby completing the SiC f Preparation of SiC composite materials.

[0041] In some embodiments, the process parameters of CVI deposition are as follows: methane CH4 is used as the precursor gas source, the deposition temperature is 800-900° C., the deposition pressure is 2-5 kPa, the deposition time is 20-50 h, and the PyC interface is deposited to a thickness of 100-300 nm.

[0042] In some embodiments, SiC is prepared by melt infiltration. f The method for forming a / SiC composite material tube layer is as follows: a SiC fiber preform with a PyC interface deposited thereon is pre-sintered at 600-800°C to stabilize the PyC interface structure, enhance the bonding force between the PyC and SiC fiber preform interface, and then immersed in molten SiC for 90-120 minutes to allow the SiC liquid to penetrate between the fibers, and then cooled to room temperature to solidify to form a densified SiC matrix.

[0043] S4. Prepare a WSi2 coating on the outer surface of the SiC / SiC composite material layer to form a second layer of WSi2 coating.

[0044] The preparation method of this step is the same as that of S2.

[0045] S5. Prepare a W-Re alloy thin-walled tube on the outer surface of the second WSi2 coating to form a second W-Re alloy layer.

[0046] The preparation method of this step is the same as that of S1.

[0047] Comparative example (without WSi2 coating) (1) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare the first layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.02mm.

[0048] (2) An automatic wire laying machine is used to prepare a SiC fiber preform outside the tungsten-rhenium alloy thin-walled tube layer. The obtained SiC fiber preform is hung on the sample rack of the vacuum furnace. The preform is located at the center of the isothermal zone in the furnace. The CVI process is used to deposit the PyC interface on the above SiC fiber. The deposition process parameters are: methane CH4 is used as the precursor gas source, the deposition temperature is 800°C, the deposition pressure is 2kPa, the deposition time is 20h, and the PyC interface with a thickness of 100nm is deposited.

[0049] (3) The SiC fiber preform with the PyC interface deposited was pre-sintered at 700°C, immersed in molten SiC for 90 min, and then cooled to room temperature to solidify to form a densified SiC matrix. f / SiC composite materials are post-processed to remove impurities on the surface of the ceramic matrix composite materials, repair possible defects, and produce 0.02mm SiC f / SiC composite material tube layer.

[0050] (4) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare the second layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.03mm.

[0051] Example 1 (1) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare the first layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.02mm.

[0052] (2) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are as follows: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. The tungsten-rhenium alloy thin-walled tube is surface polished, cleaned and dried. In a hot press furnace, the ball-milled WSi2 powder is pre-placed on the tungsten-rhenium alloy thin-walled tube for sintering. The sintering temperature is 1500℃ and the sintering time is 2h. Repeat the sintering steps many times until the first layer of WSi2 coating with a thickness of 0.01mm is sintered on the surface of the tungsten-rhenium alloy tube.

[0053] (3) First, an automatic fiber laying machine is used to prepare a SiC fiber preform outside the first layer of WSi2 coating, and the obtained SiC fiber preform is hung on the sample rack of the vacuum furnace. The preform is located at the center of the isothermal zone in the furnace, and the PyC interface is deposited on the above SiC fiber using the CVI process. The deposition process parameters are: methane CH4 is used as the precursor gas source, the deposition temperature is 800℃, the deposition pressure is 2kPa, the deposition time is 20h, and the PyC interface with a thickness of 100nm is deposited.

[0054] (4) The SiC fiber preform with the PyC interface deposited was pre-sintered at 700°C, immersed in molten SiC for 90 min, and then cooled to room temperature to solidify to form a densified SiC matrix. f / SiC composite materials are post-processed to remove impurities on the surface of the ceramic matrix composite materials, repair possible defects, and produce 0.02mm SiC f / SiC composite material tube layer.

[0055] (5) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. In a hot press furnace, f The WSi2 powder after ball milling was pre-placed on the SiC composite material for sintering at a sintering temperature of 1500℃ for 2h. The sintering steps were repeated several times until the SiC f A second layer of WSi2 coating with a thickness of 0.02 mm was sintered on the surface of the / SiC composite material.

[0056] (6) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare a second layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.03mm.

[0057] Example 2 (1) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare the first layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.02mm.

[0058] (2) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are as follows: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. The tungsten-rhenium alloy thin-walled tube is surface polished, cleaned and dried. In a hot press furnace, the ball-milled WSi2 powder is pre-placed on the tungsten-rhenium alloy thin-walled tube for sintering. The sintering temperature is 1500℃ and the sintering time is 2h. Repeat the sintering steps many times until the first layer of WSi2 coating with a thickness of 0.02mm is sintered on the surface of the tungsten-rhenium alloy tube.

[0059] (3) First, an automatic fiber laying machine is used to prepare a SiC fiber preform outside the first layer of WSi2 coating, and the obtained SiC fiber preform is hung on the sample rack of the vacuum furnace. The preform is located at the center of the isothermal zone in the furnace, and the PyC interface is deposited on the above SiC fiber using the CVI process. The deposition process parameters are: methane CH4 is used as the precursor gas source, the deposition temperature is 850℃, the deposition pressure is 3kPa, the deposition time is 30h, and the PyC interface with a thickness of 200nm is deposited.

[0060] (4) After pre-sintering the SiC fiber preform at 700°C, immerse it in molten SiC for 100 min, and then cool it to room temperature to solidify it to form a densified SiC matrix. f / SiC composite materials are post-processed to remove impurities on the surface of the ceramic matrix composite materials, repair possible defects, and produce 0.02mm SiC f / SiC composite material tube layer.

[0061] (5) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. In a hot press furnace, f The WSi2 powder after ball milling was pre-placed on the SiC composite material for sintering at a sintering temperature of 1500℃ for 2h. The sintering steps were repeated several times until the SiC f A second layer of WSi2 coating with a thickness of 0.02 mm was sintered on the surface of the / SiC composite material.

[0062] (6) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare a second layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3, thickness is 0.03mm.

[0063] Example 3 (1) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare the first layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.015mm.

[0064] (2) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are as follows: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. The tungsten-rhenium alloy thin-walled tube is surface polished, cleaned and dried. In a hot press furnace, the ball-milled WSi2 powder is pre-placed on the tungsten-rhenium alloy thin-walled tube for sintering. The sintering temperature is 1500℃ and the sintering time is 2h. Repeat the sintering steps many times until a WSi2 coating with a thickness of 0.01mm is sintered on the surface of the tungsten-rhenium alloy tube.

[0065] (3) First, an automatic fiber laying machine is used to prepare a SiC fiber preform outside the first layer of WSi2 coating, and the obtained SiC fiber preform is hung on the sample rack of the vacuum furnace. The preform is located at the center of the isothermal zone in the furnace, and the PyC interface is deposited on the above SiC fiber using the CVI process. The deposition process parameters are: methane CH4 is used as the precursor gas source, the deposition temperature is 950℃, the deposition pressure is 4kPa, the deposition time is 35h, and the PyC interface with a thickness of 300nm is deposited.

[0066] (4) After pre-sintering the SiC fiber preform at 700°C, immerse it in molten SiC for 120 min, and then cool it to room temperature to solidify it to form a densified SiC matrix. f / SiC composite materials are post-processed to remove impurities on the surface of the ceramic matrix composite materials, repair possible defects, and produce 0.02mm SiC f / SiC composite material tube layer.

[0067] (5) Put WSi2 powder and steel balls into a ball mill, add anhydrous ethanol, and ball mill the WSi2 powder. The ball milling parameters are: ball milling time 4h, ball milling speed 500r / min. After ball milling, filter the ball milling liquid to separate the WSi2 powder, and then dry it in an oven. The drying process is: first dry at 60℃ for 24h, and then dry at 110℃ for 12h. In a hot press furnace, fThe WSi2 powder after ball milling was pre-placed on the SiC composite material for sintering at a sintering temperature of 1500℃ for 2h. The sintering steps were repeated several times until the SiC f A second layer of WSi2 coating with a thickness of 0.02 mm was sintered on the surface of the / SiC composite material.

[0068] (6) Prepare a tungsten-rhenium alloy cylindrical billet with a rhenium content of 25%, and use a cold rolling process to prepare a second layer of tungsten-rhenium alloy thin-walled tube layer. The density of the tungsten-rhenium alloy tube layer is 19.65 g / cm 3 , thickness is 0.03mm.

[0069] Performance test of the cladding tube for lithium-cooled space nuclear reactor in the above embodiments and comparative examples: The erosion corrosion performance test of the cladding tube for lithium-cooled space nuclear reactor was carried out by liquid metal rotary corrosion device, and the air tightness test of the cladding tube sample was carried out by helium positive pressure holding test. During the erosion corrosion performance test, the temperature of the liquid lithium on the outer surface of the cladding tube was 1200℃, the temperature of the uranium on the inner surface of the cladding tube was 650℃, the flow rate of liquid lithium was 9.4kg / s, and the corrosion time was 2000h; during the air tightness test, 15MPa helium positive pressure was used for 100 hours, and the test results are shown in the following table.

[0070]

[0071] The results show that the corrosion weight loss and helium leakage rate of the cladding tube samples containing WSi2 transition coating (Examples 1-3) are significantly reduced compared with those of the samples without transition coating (Comparative Example). f The thickness of the reaction layer formed by the reaction of WC2 with SiC is significantly reduced. And the different thicknesses of tungsten-rhenium alloys have a significant effect on protecting SiC. f / SiC composites have different corrosion effects when subjected to UO2 and liquid lithium corrosion.

[0072] This not only shows that the WSi2 transition coating can effectively improve the lithium corrosion resistance and air tightness of the cladding tube sample for lithium-cooled space nuclear reactor in the above embodiment, but also shows that the appropriate thickness of tungsten-rhenium alloy can effectively protect SiC f / SiC composite materials are subject to corrosion by UO2 and liquid lithium, thereby ensuring both the corrosion resistance and airtightness of the cladding tube and the lightweight degree of the cladding tube.

[0073] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A cladding tube for a lithium-cooled space nuclear reactor, characterized in that: The cladding tube is composed of a first layer of W-Re alloy layer, a first layer of WSi2 coating, a SiC f The / SiC composite material layer, the second WSi2 coating layer and the second W-Re alloy layer are stacked to form a sandwich structure.

2. The cladding tube for a lithium-cooled space nuclear reactor according to claim 1, characterized in that: The mass fraction of rhenium in the W-Re alloy is 20-30%.

3. The cladding tube for a lithium-cooled space nuclear reactor according to claim 1, characterized in that: The thickness of the first W-Re alloy layer and the second W-Re alloy layer are 0.015-0.02 mm and 0.02-0.04 mm respectively; f The thickness of the / SiC composite material layer is 0.01-0.03mm.

4. The cladding tube for a lithium-cooled space nuclear reactor according to claim 1 or 3, characterized in that: The thicknesses of the first WSi2 coating layer and the second WSi2 coating layer are 0.01-0.02 mm and 0.02-0.03 mm respectively.

5. A method for preparing a cladding tube for a lithium-cooled space nuclear reactor according to any one of claims 1 to 4, characterized in that: The steps include: S1. Preparing a W-Re alloy thin-walled tube to form a first W-Re alloy layer; S2. Preparing a WSi2 coating on the outer surface of a W-Re alloy thin-walled tube to form a first layer of WSi2 coating; S3. Coating SiC on the first WSi2 coating f / SiC composite material layer; S4. Preparing a WSi2 coating on the outer surface of the SiC / SiC composite material layer to form a second layer of WSi2 coating; S5. Prepare a W-Re alloy thin-walled tube on the outer surface of the second WSi2 coating to form a second W-Re alloy layer.

6. The preparation method according to claim 5, characterized in that: S2 includes: Pre-place ball-milled WSi2 powder on a W-Re alloy thin-wall tube and sinter, repeating this process multiple times until a first layer of WSi2 coating of a desired thickness is formed; S4 includes: pre-placing ball-milled WSi2 powder on the SiC / SiC composite material layer and sintering, and repeating the process multiple times until a second WSi2 coating layer of a desired thickness is formed.

7. The preparation method according to claim 6, characterized in that: The sintering temperature is 1200-1800°C and the sintering time is 2-3h.

8. The preparation method according to claim 5 or 6, characterized in that: S3 includes: weaving a SiC fiber preform on the outer surface of the first layer of WSi2 coating, then depositing a pyrolytic carbon PyC interface on the SiC fiber preform using a CVI process, and then densifying the SiC fiber preform matrix using a melt infiltration method to prepare a SiC matrix.

9. The preparation method according to claim 8, characterized in that: The CVI process has a deposition temperature of 800-900° C., a deposition pressure of 2-5 kPa, a deposition time of 20-50 h, and deposits a PyC interface with a thickness of 100-300 nm.

10. The preparation method according to claim 9, characterized in that: The melt infiltration method comprises: pre-sintering a SiC fiber preform with a PyC interface deposited thereon at 600-800° C., immersing the preform in molten SiC for 90-120 minutes, and then cooling and solidifying the preform to form a densified SiC matrix.

Citation Information

Patent Citations

  • Densification method for high-temperature antioxidant coating of tungsten-rhenium thermocouple

    CN108034939A

  • Nuclear reactor annular fuel damage experimental device and experimental method

    CN110517797A

  • Dual-mode space nuclear reactor core

    CN113409962A

  • Multi-layer cladding tube and preparation method thereof

    CN113571209A

  • Space nuclear power system adopting multi-stage heat exchange power shielding heat exchanger and circulation method

    CN113871038A

Cited By

  • Thermal conducting wire, thermal conducting wire preparation method and equipment

    CN121344446A